2021
DOI: 10.1002/adma.202103476
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Devil's Staircase Magnetization from Tunable Charge Density Waves in Nonsymmorphic Dirac Semimetals

Abstract: While several magnetic topological semimetals have been discovered in recent years, their band structures are far from ideal, often obscured by trivial bands at the Fermi energy. Square‐net materials with clean, linearly dispersing bands show potential to circumvent this issue. CeSbTe, a square‐net material, features multiple magnetic‐field‐controllable topological phases. Here, it is shown that in this material, even higher degrees of tunability can be achieved by changing the electron count at the square‐net… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 74 publications
(122 reference statements)
2
36
0
Order By: Relevance
“…It was proposed to host the antiferromagnetic skyrmion phase, which is not yet been confirmed . Similar substitution can be done for CeSbTe, where it leads to evolution of complex magnetization curves (Devil’s staircase magnetization) originated from perturbing of magnetic interactions along the c -axis. …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was proposed to host the antiferromagnetic skyrmion phase, which is not yet been confirmed . Similar substitution can be done for CeSbTe, where it leads to evolution of complex magnetization curves (Devil’s staircase magnetization) originated from perturbing of magnetic interactions along the c -axis. …”
Section: Introductionmentioning
confidence: 91%
“…15 Similar substitution can be done for CeSbTe, where it leads to evolution of complex magnetization curves (Devil's staircase magnetization) originated from perturbing of magnetic interactions along the caxis. [16][17][18] Despite the growing interest to CeSbTe and GdSbTe members of the LnSbTe series, there are only fragmentary reports on physical properties related with topology, ARPES measurements and crystal structures of the other lanthanide members. The recent reports on HoSbTe [19][20][21] hint to a narrow band gap driven by spin-orbit coupling, a bad-metal-like state observed in resistivity measurements and an antiferromagnetic transition due to ordering of the Ho 3+ moments.…”
Section: Introductionmentioning
confidence: 99%
“…Topological materials of recent research interest are square-net semimetals in the ZrSiS family. , The relevant electronic structure of these materials derives from partially filled p x and p y orbitals that form a two-dimensional (2D) square planar bonding lattice. Despite a wealth of strongly correlated and magnetic phases in these materials, tight-binding models have demonstrated remarkable success in predicting the relevant electronic structure in square-nets; in fact, it appears that the topological classification across the entire family can be largely predicted via a simple ratio of bond lengths inside and outside the square-net . We will demonstrate that the electronic structure of the three-dimensional (3D) cubic metal LaIn 3 can be understood in terms of a chemically analogous tight-binding model with primary p x , y contributions.…”
Section: Introductionmentioning
confidence: 91%
“…This allows for opportunities to observe new topological states through the breaking of time-reversal symmetry, leveraging magnetic order as another tunable parameter to control electronic structure and access multiple topologically distinct phases.LnSb x Te 2−x−δ (δ indicating vacancy concentration in the square net) materials also exhibit charge density waves (CDWs), which are coupled with structural dis-tortions in the square-net that evolve continuously with Sb/Te composition, and are a result of changes in band filling within the square net. [20][21][22] We have recently reported that the CDW is responsible for the gapping of topologically trivial states in GdSb 0.46 Te 1. 48 , yielding an ideal nonsymmorphic Dirac semimetal band structure free of all other states about E F , separated by hundreds of meV.…”
Section: Introductionmentioning
confidence: 99%